EFEKTIFITAS PENDIDIKAN KESEHATAN METODE DEMONSTRASI DAN MEDIA VIDEO TERHADAP PRAKTIK SADARI DI PONDOK PESANTREN DARUL HIJRAH PUTRI MARTAPURA - Ruslinawati Ruslinawati; Darmayanti Wulandatika; Nisrina Nadya Wahda (LPPM - Universitas Muhammadiyah Banjarmasin, 2020)
Early detection of breast cancer with BSE can be done alone to recognize abnormalities in the breast, carried out periodically every month, on the 7th to 10th day after menstruation, the actions include: position, inspection, palpation and patterns. However, there are still many who do not know about BSE and the high number of breast cancer cases in 2018 reaching 542 cases in Indonesia. To reduce the high cases of breast cancer, health education about BSE needs to be done. Analyze the effectiveness of health education demonstration methods and video media on BSE practices. The Quasy Experimental research design, the Posttest Only Control Group Design, the total population of class XI is 216 students were taken by the Proportional Stratified Random Sampling Method with 68 people divided into demonstration with video groups and video groups, the statistical test results using the Mann Whitney test. There is a significant difference in effectiveness between health education demonstration methods with video media and video media only, where the p value is 0.033 <0.05. Demonstration health education with video media is more effective against BSE practices than health education with video media only.